Pengaruh Teknik Gelpitas terhadap Kemampuan Berbicara Bahasa Inggris Anak Usia 5-6 Tahun di TKI Negeri Pembina Kota Tasikmalaya - Prifiantari, Siska; Elan, Elan; Yamin, Alfian Azhar (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
The scarcity of research on English-speaking skills among children aged 5–6 years, particularly regarding vocabulary mastery, underlies this study. The research aims to evaluate the effectiveness of the Gelpitas technique in assisting children aged 5–6 years in speaking English. A pre-experimental design with a One-Group Pretest–Posttest model was employed, involving 15 group B students selected using a saturated sampling technique. Data were collected through observation and analyzed using descriptive statistics and the Wilcoxon test in SPSS 25. The results indicate that H₀ was rejected and H₁ was accepted, with an Asymp. Sig. (2-tailed) value of 0.001 < 0.05. These findings demonstrate that the application of the Gelpitas technique significantly improves the English-speaking skills of children aged 5–6 years.